2005
DOI: 10.1080/00140130500101064
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals' perspectives in exercise referral: implications for the referral process

Abstract: The number of exercise referral schemes expanded rapidly across the UK during the 1990s. Health professionals are thought to be one of the most credible sources of health advice for patients and, hence, are thought to have a pivotal role to play in exercise referral schemes. The aim of the study was to investigate the exercise referral process from the health professional's perspective, specifically examining perceived barriers to referral, priority given to an exercise referral scheme in day-to-day consultati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 19 publications
3
55
0
3
Order By: Relevance
“…As a result, a recommendation from a GP might improve or even be necessary for uptake and attendance [29]. On the other hand, some health professionals perceive barriers to referral [30,31] and do not prioritise physical activity promotion. Therefore, they may be far more reluctant to promote schemes in comparison with researchers who have a vested interest in recruitment.…”
Section: Recruitmentmentioning
confidence: 99%
“…As a result, a recommendation from a GP might improve or even be necessary for uptake and attendance [29]. On the other hand, some health professionals perceive barriers to referral [30,31] and do not prioritise physical activity promotion. Therefore, they may be far more reluctant to promote schemes in comparison with researchers who have a vested interest in recruitment.…”
Section: Recruitmentmentioning
confidence: 99%
“…This links back to the need for implementing a system to allow communication between physicians and FPs. Studies have found that physicians are hesitant to refer patients for exercise to FPs because they do not have any way to follow up on the patient's progress [13,16]. By including a progression and follow up section on the prescription pad, EIM can close the communication gap between FPs and physicians.…”
Section: Theme 4: Informing the Environment About Eimmentioning
confidence: 99%
“…Studies have examined how to improve the exercise prescription and referral procedure from the perspective of physicians [9,11,12,16,17], yet EIM believes both physicians and FPs are key members in promoting and implementing the inclusion of exercise in the healthcare system [5]. By conducting a focus groups with personal trainers employed at a campus recreation facility, we are the first pilot study to document information from the perspective of FPs.…”
Section: Theme 4: Informing the Environment About Eimmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Running is a fundamental exercise which enhances many aspects associated with health. During the running gait cycle, initial loading of the limb occurs in the early part of the support phase as a result of the foot's collision with the ground at footstrike.…”
Section: Introductionmentioning
confidence: 99%